2021
DOI: 10.1016/j.sjbs.2021.07.089
|View full text |Cite
|
Sign up to set email alerts
|

Logit model in prospective coronary heart disease (CHD) risk factors prediction in Saudi population

Abstract: Analysis through logistic regression explored to investigate the relationship between binary or multivariable ordinal response probability and in one or more explanatory variables. The main objectives of this study to investigate advanced prediction risk factor of Coronary Heart Disease (CHD) using a logit model. Attempts made to reduce risk factors, increase public or professional awareness. Logit model used to evaluate the probability of a person develop CHD, considering any factors such as age, gender, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…The prevalence of HT among the participants in the study was found to be much higher than the world average. However, the results are closer to the prevalence found in the country where the study was conducted (15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of HT among the participants in the study was found to be much higher than the world average. However, the results are closer to the prevalence found in the country where the study was conducted (15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 74%
“…Second, the extensive array of clinical tests and examination protocols for this population overcomes the limitations associated with incomplete data in some physical examinations of the general population. Various models for com-mon diseases include logistic regression models, classification tree models, backpropagation (BP) neural networks, and nomograms [15][16][17][18]. In this study, we opted to create a nomogram for identifying ASCVD in T2DM patients due to its advantages in risk factor screening, consideration of interaction terms, and risk assessment [19].…”
Section: Discussionmentioning
confidence: 99%
“…The research chooses factors such as age, gender, the measure of cholesterol, blood pressure, family history, smoking etc. and use some basic methods in logistic regression model to find out the relationship between the variables [1]. Thirugnanam et.al conducted research to find out the most influential factors as well as build an accurate prediction model using methods such as support vector machine, decision tree and logistic regression [2].…”
Section: Introductionmentioning
confidence: 99%